Antifungal Activity of Propolis Ethanol Extract Against Botrytis cinerea, Altrnaria sp Which Caused Many Plant Diseases - Darweesh, A. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was conducted to determine the effect of different concentrations of ethanol extract of propolis against two fungi Botrytis cinerea, Altrnaria sp. The most important chemical constituents of propolis diagnosed by the Infra Red Spectroscopy, were the Flavonoids specificaly. Results showed a high antifungal activity of ethanol extract of propolis, evidently with a high concentration of extract (5) mg, which completely inhibited the radial growth on both solid and liquid media (PDA &PD Broth ) of both fungi . We observed that , ethanol extract propolis at concentration of 5 mgwere sprayed on experimental infection on some plants (eggplant leavers & cucumber ) which were effected by fungal. The spraying of ethanol extract of propolis before 24, 48 hour prevented development of disease and made a good protection of the mentioned plants from being infected with this fungus. While, the ability of fungus to grow after 24, 48 hours from ethanol extract of propolis treatment was reduce markedly as compared with control ,such treatment show a slow growth of pathogen infect.